Design of an Integrated Controller based on ZigBee Wireless Network - Zhongbao Ji (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
There are many different home appliances in our home, for example Lamps, Television, DVD player, etc. Moreover, the appliances are usually controlled by different controller using IR (Infra-Red) signal. This brings our life many inconveniences, and many resources are wasted. Therefore, we propose an integrated controller. It can control these various appliances, only a single one. In order to realize the purpose, the integrated controller must have previous preparations, because the appliances have their different IR controlling signals. Therefore, the integrated controller must “learn” the IR signals from their own controllers, and save them inside. Because the radiation range of IR signal is limited, and the appliances are distributed in different rooms, we propose a novel wireless network based on IEEE802.15.4, especially ZigBee protocol, to transmit the controlling signals from the integrated controller. The proposed scheme consists of two main parts. The one part is the hardware design, include the integrated controlled with ZigBee transmission device and the terminal control module with ZigBee-IR conversion, which converts a control signal transferred through the ZigBee network into an IR typed control signal. The terminal control module is based on CC2430 as the controller core. The other is the software design. The software part uses IAR Embedded Workbench. Based on Zstack-1.4.2-1.1.0 protocol provided by TI, man can program the control codes of the system. The proposed scheme can also provide the well-defined interface and the necessary basis for preparing the smart home system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3043